Syringe Service Program Utilization, Barriers, and Preferences for Design in Rural Appalachia: Differences between Men and Women Who Inject Drugs. (29th July 2020) - Lancaster, Kathryn E.; Cooper, Hannah L. F.; Browning, Christopher R.; Malvestutto, Carlos D.; Bridges, John F. P.; Young, April M.
Abstract: Background People who inject drugs (PWID) in rural areas of the United States have had limited access to syringe service programs (SSP). Rural SSP have recently surged, but accompanying research is lacking about PWID utilization, barriers, and preferences for SSP design and how those preferences vary by gender. Methods: Interviewer-administered surveys elicited information about utilization, barriers, and preferences for SSP design from 234 PWID recruited using respondent-driven sampling in Appalachian, Kentucky. Gender differences among reported barriers to utilizing SSP and preferences for program design were explored using Mantel-Haenszel chi-square tests. Results: Overall, 49% of PWID had ever utilized an SSP. The most common reasons for not utilizing an SSP were lack of awareness (23%), fear of being seen or disclosing drug use (19%), and lack of need (19%). The most preferred SSP design was located within a health department (74%) and operating during afternoon hours (66%). Men were more likely than women to prefer SSP in health departments (80% vs. 65%, p = 0.01), while more women than men preferred staffing by health department personnel (62% vs. 46%, p = 0.02). Women were less likely to favor evening hours (55% vs. 70%, p = 0.02). Fewer women wanted SSP nurses (78% vs. 90%, p = 0.01), social workers (11% vs. 24%, p = 0.01), or people who use drugs (20% vs 34%, p = 0.02) to staff SSP. Conclusions: Despite recent scale-up, SSP in Appalachia remain under-utilized. PWID were open to a range of options for SSP design and staffing, though there were variations by gender. Implementation research that identifies best strategies for tailored SSP scale-up in rural settings should be considered.